Long-term work contracts versus sequential spot markets: Experimental evidence on firm-specific investment - Vital Anderhub; Manfred Königstein; Dorothea Kübler (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Dismissal rules, i.e. legally enforced long term contracts, have beem defended against criticism for, among other things, providing efficient incentives to invest in relationship specific skills. However, in many situations efficient investment can also be attained by spot contracts. We replicate such a situation with our experimental design based on a simple two period game, involving the choke of the contract; length by the principal and an investment choke by the agent. In contrast to the game theoretic predictions, we find that investment of the worker and length of contract; are strictly positively correlated. We interpret our finding as an indication for a perceived market risk due to other players' actions although the model is fully deterministic. This could imply a behaviorally relevant difference between contract and market administered incentives.
urn:nbn:de:kobv:11-10046302
Keywords: D82; D83; J41; J64; 330; principal agent; experiment; specific human capital